Senior High School Students’ Perception of Physical Education Teachers - Priyono, Bambang; Rozi, Fatkhur; Hanani, Endang Sri (Jurnal Cakrawala Pendidikan, 2023)
The objective of this research is to examine the perception of senior high school students in Indonesian in interpreting physical education teachers. This research used a mixed method and descriptive analysis. Qualitative data were collected from questionnaire by completing the statement "my physical education teacher...?". Quantitative data were produced from the total amount of most frequently used words. The total respondents were 237 Indonesian students who were chosen randomly based on their willingness to fill in the questionnaire prepared and participants were then determined using a purposive sampling technique. The data were analyzed under the noticing, collecting, and thinking about interesting things phases. The results show the frequently used words were: "˜kind’, "˜cool’, "˜cheerful’, "˜friendly’, and "˜firm’. The other results show some words with negative meaning, including: ’infrequently present’, ’annoying’, ’difficult’, and ’fierce’. The term ’ex-’ shows non-professional competence. This research finds that the Physical Education teachers were kind, friendly, and patient, delivering lesson passionately and with fun and showed discipline, showing that the Physical Education teachers were reflected as the need for teacher’s competence. However, the negative words appearing limitedly in the questionnaire still require more attention.